REVIEW: REVIEW ARTICLE LIPID-BASED NANOTECHNOLOGY - Garnadi Jafar; R. Awaludin Nazal N; Entris Sutrisno (Medical Sains : Jurnal Ilmiah Kefarmasian, 2024)
Nanotechnology is defined as engineering the creation of materials, functions, and devices on the nanometer scale. Nanoscience is increasingly developing and becoming a part of various fields, such as electronics, materials, and biology. Lipid nanoparticles are a major application in nanotechnology. In formulas II and III, smaller results were obtained compared with the other formulas. Based on the results of this study, it can be concluded that the nanostructured lipid carrier system with solid lipid poloxamer and stearic acid with liquid soybean oil lipids obtained good characteristics, and each test met the range. From the explanation above, it can be concluded that lipid-based nanotechnology has great potential in various fields such as medicine, cosmetics, and agriculture. Its use can provide great benefits such as increasing the effectiveness of drug administration, increasing the absorption of nutrients in food, and developing cosmetic products. which one is safer and more effective. To compare several types of nanoparticle methods, such as Liposomes, Neosomes, Etosomes, SLN, and NLC for selection of the lipid base, namely NLC. It is important to ensure that the use and development of this technology are safe and beneficial for humans and the environment. Keywords : Nanotechnology, Nanoparticles, Lipid-Based Nanoparticles